Trigger Finger Release by Retinaculotome Pushing Knife: Technique and Case Report - Rezende, Luis Guilherme Rosifini Alves; Shimaoka, Filipe Jun; Shimabukuro, Gunter Shin Iti Takamori; Mandarano-Filho, Luiz Garcia; Mazzer, Nilton (ARCHIVES OF HEALTH INVESTIGATION, 2022)
The trigger finger is a common affection commonly in the daily hand surgeon attending. The management began with non-operative methods. The absence of improvement could appoint to different operative techniques, such as open release, mini-open approaches, and percutaneous needle approaches. With respect to the open surgical approach, there are many alternatives to release the A1 Pulley, such as scalpel, pushing knives, or scissors. This study aims to present a Retinaculotome designed as a Modified Pushing Knife, to release the A1 Pulley for the management of the trigger finger.